Complexes of 3,4-dimethoxybenzoic acid anion with Cu(II), Co(II), La(III), and Nd(III) - Ferenc, Wieslawa; Czapla, Katarzyna; Sarzyński, Jan; Zwolinska, Anna (Eclética Química, 2007)
Physico-chemical properties of 3,4-dimethoxybenzoates of Co(II), Cu(II), La(III) and Nd(III) were studied. The complexes were obtained as hydrated or anhydrous polycrystalline solids with a metal ion–ligand mole ratio of 1 : 2 for divalent ions and of 1 : 3 in the case of trivalent cations. Their colours depend on the kind of central ion: pink for Co(II) complex, blue for Cu(II), white for La(III) and violet for Nd(III) complexes. The carboxylate groups in these compounds are monodentate, bidentate bridging or chelating and tridentate ligands. Their thermal decomposition was studied in the range of 293–1173 K. Hydrated complexes lose crystallization water molecules in one step and form anhydrous compounds, that next decompose to the oxides of respective metals. 3,4 – Dimethoxybenzoates of Co(II) is directly decomposed to the appropriate oxide and that of Nd(III) is also ultimately decomposed to its oxide but with the intemediate formation of Nd 2 O 2 CO 3. . The magnetic moment values of 3,4–dimethoxybenzoates determined in the range of 76–303 K change from 4.22 μ B to 4.61 μ B for Co(II) complex , from 0.49 μ B to 1.17 μ B for Cu(II) complex , and from 2.69 μ B to 3.15 μ B for Nd(III) complex.